Nationalism and Muslim identity: An Examination of the Axiology of Islamic Education - Edi Sundowo; Salminawati; Usiono; Amsal Qori Dalimunthe; Neng Nurcahyati Sinulingga (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2023)
Nationalism and Islamic identity are two concepts that are interrelated and important for Islamic education. Nationalism is an attitude of love for the homeland and nation that does not conflict with Islamic teachings as long as it does not contain fanaticism, chauvinism or superiority. The identity of a Muslim is a servant of God who surrenders to Him wholeheartedly, follows the teachings of Islam revealed by the Prophet Muhammad SAW, and strives to be a witness to truth and goodness in the world. Islamic education is a comprehensive process of developing human potential in accordance with Islamic values. Axiology of Islamic education is topics related to the purpose, objectives and values of Islamic education. The purpose of this research is to analyze the relationship and influence of nationalism and Islamic identity in the study of the axiology of Islamic education. This research uses library research, and the final results are analyzed interactively by presenting descriptive research discussions. The results of this study show that nationalism and Muslim identity can be strengthened and realized through Islamic education that is oriented towards values such as tawhid, worship, morals, knowledge, charity and da'wah. Islamic education can also make a positive contribution to nation and state building as well as global cooperation and peace by respecting diversity and universal values in accordance with Islamic law. Keywords: Nationalism, identity, Axiology, Islamic Education